Análisis del proceso de comunicación del Sindicato de Choferes del cantón Catamayo, durante el 2024 - Riofrio Iles, Diana Estefania (2024)
This study analyzes the communication process of the Sindicato de Choferes del cantón Catamayo during 2024, managed in an unplanned manner by the administrative staff. The objective is to identify applicable organizational communication models and diagnose the union's communication needs. The research, conducted in May and June 2024 in Catamayo, employed a qualitative approach, using interviews, focus groups and SWOT analysis. The results show that communication is managed through traditional media, such as billboards and rolling megaphones, targeting older members, while younger members are informed through digital platforms, such as Facebook. However, the communication process follows a top-down vertical structure, which limits continuous feedback and active member participation. Although partners perceive communication as generally effective, key areas for improvement were identified, such as a lack of consistency in messaging and the need to professionalize communication management. A key recommendation is the creation of a specialized communication department, which would allow for more strategic planning and execution of internal and external communication processes. In conclusion, it is recommended that the communication of the Sindicato de Choferes del cantón Catamayo be managed by professionals in the area. The implementation of a specialized department would contribute to greater organizational efficiency, improving the coherence and clarity of messages, adapting to the needs of different age groups of members, and promoting a more effective and bidirectional communication that strengthens the cohesion and overall functioning of the organization. Key words: Communication organizational communication - communication processes - communication channels - communication diagnostics - drivers' union.